Interações ecológicas entre a macrófita invasora lírio-do-brejo (Hedychium coronarium – J. Köenig, 1783) e macroinvertebrados aquáticos de zona litoral: implicações na estruturação comunitária e herbivoría - Saulino, Hugo Henrique Lanzi (2017)
Biological invasions are the main cause of biodiversity erosion, which is widespread in several invasive species that have antropogenic interference as a key process. Invasive macrophyte species can shift structures of associated communities, and they can interfere in many ecological process in aquatic ecosystems. For these issues, macroinvertebrate taxonomic and functional analyses can show the ecological alteration processes that occur between macrofauna and these plant species. Through the surveys performed at the Fazzari reservoir (Universidade Federal de São Carlos), the potential impact of the invasive macrophyte white ginger lily (Hedychium coronarium - J. Köenig, 1783) on the taxonomic and functional diversity of freshwater macroinvertebrates dwelling the littoral zone of the reservoir was assessed. In chapters I and II of this doctoral thesis, habitat alterations caused by the white ginger lily are explored and its effect on the role of the habitat in aquatic insect assemblages is discussed. Chapters III and IV explore aspects of the resource quality of white ginger lily on associated macroinvertebrates. The final experiment also assess the implication of the resource quality provided by white ginger lily in the taxonomic and functional changes of herbivore species and their effect on macroinvertebrate food webs. The main impact of this invasive macrophyte species on the functional and structure assemblage of macroinvertebrates was related to habitat alterations caused because of white ginger lily’s faster vegetative growth. Its presence in the littoral zone seemed to show an important influence on the aquatic insect structure assemblages as well as on habitat losses. Through lower functional diversity indices and significant participation of predator larvae in the invaded reservoir banks, it was possible to infer that this invasive macrophyte promoted higher habitat complexity and lower band loss in the littoral zone. For its allochtthonous resource quality aspects, its leaves demonstrated better quality when compared with the native pickerelweed (Pontederia cordata – L.), which presents similar ecological characteristics. The higher quality resource of this invasive macrophyte was shown to be an important factor to generalist herbivore species, which differed in taxonomic composition of specialist herbivore species present in the native macrophyte leaves. Although invasive and native macrophyte species seemed to support similar macroinvertebrates structures, which were composed mainly of omnivore species, pickerelweed leaves, which are of lower nutritional quality, were shown to be unfavorable to the herbivore species. The leaf chemical traits of the native species, such as lower N% and higher P% and polyphenols, negatively influenced the herbivore functional richness, as well as caused a decrease in predator-prey rations in the food web structure. This indicated a bottom-up effect. The results suggest that the role of macrophytes in the habitat and resource quality provided by macrophyte leaf species has an important influence on the life history of macroinvertebrates and freshwater herbivores, which in turn directly interfere with changes in the entire macroinvertebrate structure. Additionally, the results highlight the importance of selecting native species with a high resource quality in restoration practices for freshwater biodiversity conservation.